Female and male speech in prose a stylistic analysis of the character portrayal in F. Sionil Jose's Ermita and Two Filipino Women - Libuit, Marigold C. (College of Arts and Letters, University of the Philippines Diliman, 1992)
This study is a descriptive analysis of the character portrayal through the female and male characters' direct speech in F. Sionil Jose's Two Filipino Women and Ermita. The Study seeks to find the relative extent to which sex differentiation is manifested in the two novels. Moreover, it seeks to observe how an analysis of the speech of the characters, focusing on the problem of the characteristic features of female and male speech can contribute to our understanding of the recurring character Ermita Rojo. The study adopts the method of analysis used by Borker and Garnica (1980). The characters' first 100 lines were analyzed against the frequency of eight stylistic features. These categories were the use of imperatives, superlatives, indirect forms, intensifiers, interjections, emotion words, affection word, and euphemisms. Ermita Rojo's speech were considered and compared with other characters' speech. These characters' spech were also compared with the speech of male character in the two texts. Results were tabulated and summarized. Surprisingly, the study yields the fact that Ermita Rojo, although a prostitute, uses more features that are markedly masculine in style. This allows F. Sionil Jose's recurring character to be more androgenous in her speech for she uses the appropriate register in achieving social goals. The study concludes that sex differentiation in language, as observed in the texts, is relative to the culture and social status of the characters. Finally, the research substantiates Borker and Garnica's (1980) descriptive theory of analysis of linguistic patterning by sex of speaker in literary prose works and dramas.